Methodological guidelines for performing laboratory works "Algorithms and data structures" - Yagup, K. V. (My University, 2023)
The effective solution of programming problems is determined not only by a successful solution algorithm, but also by the correct choice of the data structure, which will allows to implement the main operations of the algorithm: addition, deletion, searching of elements, definition the sequence of their processing. Algorithm and data structure are inextricably linked, because a decision about data structuring cannot be made without knowledge of the algorithms that will be applied, and vice versa, the choice of algorithm significantly depends on the data structure. Methodological instructions for laboratory works consider the following topics: stack and queue and their program organization, dynamic programming, greedy algorithms, algorithms for generating pseudorandom numbers, basic sorting methods, namely bubble sort, selection sort, insertion sort, quick sort, Shell sort, merge sort, heap sort. For all works, detailed instructions have been drawn up regarding the software implementation of relevant algorithms and data structures, basic theoretical information and examples with illustrations have been provided. The C++ programming language is used for laboratory work. When performing laboratory work, it is necessary to write a corresponding program with the names of variables and functions that are proposed in the methodological instructions and make a report. The report should contain: 1. Description of the program 2. The values of the variables during the execution of the entire program 3. Block schemes 4. Appropriate explanations Also, at the end of each laboratory work, there are control questions on the corresponding topic for students to consolidate their knowledge.
Keywords: methodological guidelines; stack data structure; information technology; software; dynamic programming